A Traceable, Sequential Multistage‐Targeting Nanoparticles Combining Chemo/Chemodynamic Therapy for Enhancing Antitumor Efficacy. (21st April 2021) - Wang, Ning; Liu, Chenyu; Yao, Weihe; Zhou, Hengjun; Yu, Simiao; Chen, Hailiang; Qiao, Weihong
Abstract: Although chemodynamic therapy (CDT) can effectively inhibit tumor growth and metastasis, it is challenging to eliminate tumors. Generally, CDT needs to combine with extra therapeutic modes for enhancing antitumor efficacy. Here, novel nanoparticles (BDTLAG NPs) are constructed via self‐assembly of cancer cell targeting prodrug (Bio‐PEG2K ‐S‐S‐CPT), organic CDT agents (TPP‐PEG2K ‐LND, TPP‐PEG2K ‐TOS), pH‐responsive prodrug (PEG2K ‐NH‐N‐DOX), T1‐enhanced magnetic resonance imaging contrast agents (Gd‐DTPA‐N16‐16), and anti‐angiogenic drug combrestatinA4 (CA4), realizing chemo(CT)‐chemodynamic combination therapy. The mechanism of BDTLAG NPs for enhancing antitumor efficacy involves: (i) BDTLAG NPs is accumulated in the tumor tissue by passive targeting; (ii) CA4 is released and specifically destroys angiogenesis, and the remaining BDTLG NPs enter the tumor cell via active targeting; (iii) the acid/glutathione (GSH)‐responsive prodrug release and GSH depletion; (iv) TPP‐PEG2K ‐LND and TPP‐PEG2K ‐TOS are accumulated in the tumor cell mitochondria due to mitochondria‐targeting, and is accompanied by endogenous reactive oxygen species bursts. This current strategy of single NPs that integrates spatiotemporally CT, CDT, GSH depletion, and MR imaging functions reflects the "all in one" concept, which provides a new opportunity for enhancing antitumor efficacy. Abstract : The combination of chemotherapy (CT) with chemodynamic therapy (CDT) can synergistically enhance therapeutic efficacy and overcome the limitations of monotherapy. The current strategy of single nanoparticles that integrate spatiotemporally CT, CDT, glutathione depletion, and magnetic resonance imaging functions reflects the "all in one" concept, which provides a new opportunity for enhancing antitumor efficacy.